2020
DOI: 10.1088/1755-1315/462/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of PLA2 and antibacterial activity test of lionfish (Pterois volitans) spine venom

Abstract: The population of Pterois volitans has caused significant damage to other fish populations and coral reef ecosystems. Population control of P. volitans consumes a considerable cost so that the utilization of these fish needs to be sought to be useful along with controlling the population. This fish is known to contain the enzyme Phospholipase A2 (PLA2), which used as an antibiotic against some bacteria. This study will examine the antibacterial activity of the phospholipase A2 enzyme extracted from P. volitans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The major achievements of the presented study were: i. The selection and implementation of the optimum protocols through literature [17] for the isolation of venom from the lionfish's thorns ii. The selection and application of the optimum protocols through literature [18] for the isolation of tetradotoxin from the muscle tissue and organs of the L.sceleratus iii.…”
Section: Discussionmentioning
confidence: 99%
“…The major achievements of the presented study were: i. The selection and implementation of the optimum protocols through literature [17] for the isolation of venom from the lionfish's thorns ii. The selection and application of the optimum protocols through literature [18] for the isolation of tetradotoxin from the muscle tissue and organs of the L.sceleratus iii.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatants were pooled. Sommeng et al (2020a) performed venom extraction of P. volitans from Indonesian sea waters to isolate phospholipase A2. In this experiment, briefly, they firstly immersed 50 g of the spine in 0.01 M phosphate buffer and 0.1 M CaCl2 for 8 min at 40℃.…”
Section: Extractions Of Crude Venom From Spinesmentioning
confidence: 99%
“…The authors also concluded that lionfish venom should be further studied for its possible pharmaceutical effects on Alzheimers' disease. Sommeng et al (2020a) determined that the coagulant activity of crude P. volitans spine venom can accelerate blood clot (procoagulant) up to 8.5 seconds. The LC-MS/MS analysis detected the procoagulant compound Nomega-nitro-L-arginine methyl ester (L-NAME).…”
Section: Bioactivities Of Venomous Spinesmentioning
confidence: 99%
“…Activity against Gram-negative bacteria has a more significant inhibition zone than Gram-positive bacteria because Gram-negative bacteria have less peptidoglycan (Zolfagharian et al, 2016). In other microorganisms, 6.29 μg of PLA2 from Acanthaster plancii can inhibit S.aureus (Gram-positive) by 8.5 mm (Ibrahim et al, 2013) and PLA2 from Pterois volitans has antibacterial activity against S. aureus with an inhibition zone of 14.35 mm (Sommeng et al, 2020).…”
Section: Antibacterial Activity Assaymentioning
confidence: 99%